Dietary arachidonic acid protects mice against the fatty liver induced by a high fat diet and by ethanol. - Karpe, F; Wejde, J; Anggård, E (1984)
Five groups of NMRI mice were fed ethanol or sucrose in a nutritionally adequate liquid diet for 9 days. The dietary fat consisted of olive oil with the fatty acid composition 18:1 77%, 18:2 10%, 18:0 and 16:0 12%. The ethanol treated groups received 5% w/v ethanol (E) or isocaloric sucrose (S). Two groups (S- and E-) received the diet without supplement. In two groups (S+ and E+) 7% of the fat was exchanged for arachidonic acid (20:4). In a fifth group (IE+) treated with ethanol and arachidonic acid the diet also contained indomethacin (10 mg/l). The mean intake of ethanol was about 20 g/kg/day. After 9 days animals were killed and liver lipids analyzed after Folch extraction. The post mortem accumulation of prostaglandin E2 in the kidney was measured by GC-MS. Dietary 20:4 was found to protect mice against fatty liver caused both by a high fat diet alone and in combination with ethanol. The liver triglycerides were 30.7 +/- 4.3 (S-), 46.1 +/- 6.9 (E-), 6.8 +/- 0.4 (S+) and 19.4 +/- 1.8 (E+). Prostaglandin levels in the kidney were depressed by ethanol treatment. Indomethacin gave variable degrees of PG synthesis inhibition. The degree of liver triglyceride accumulation in the IE+ group was inversely proportional to the degree of PG synthesis. The data suggest a role for liver 20:4 cyclooxygenase metabolites in fatty liver caused by high fat diets and ethanol.